THE LAW ENFORCEMENT OF REMOVAL CONTENT'S GAS CANISTER CRIMINAL BASED ON DECISION NUMBER: 322/PID.SUS/2020/PN.MLG - Wiraputri, Gecilla Vanda; Suyono, Yoyok Ucuk (jfpublisher, 2023)
The fulfillment of LPG needs for household needs is by selling LPG at an appropriate price set by the government. Unfortunately, many businesses try to make a profit by transmitting the contents of subsidized LPG to non-subsidized LPG which is then sold to consumers at non-subsidized prices. The objective of this research is to understand and analyze the legal liability and law enforcement of Criminal Removal Content's Gas Canister based on Decision Number 322/Pid.Sus/2020/PN.Mlg. This research is included in normative legal research. The results indicated that Iwan Agus Susanto and Hendik Dwi Susanto can be held criminally liable because they have fulfilled all the elements of criminal liability. Law enforcement of the perpetrators of criminal gas canister removal committed by defendants Iwan Agus Susanto and Hendik Dwi Susanto in the existence of facts, such as the statements of witnesses and the existence of evidence confiscated with the confession of the defendants, then law enforcement concluded that the actions committed by Iwan Agus Susanto and Hendik Dwi Susanto were proven to have violated Article 53 letter d of Law of the Republic of Indonesia No. 22/2001 concerning Oil and Gas jo Article 55 Paragraphs (1) to 1 Criminal Code.